2021
DOI: 10.3390/ph14090852
|View full text |Cite
|
Sign up to set email alerts
|

Doxycycline Attenuates Cancer Cell Growth by Suppressing NLRP3-Mediated Inflammation

Abstract: NLR family pyrin domain containing 3 (NLRP3) inflammasome formation is triggered by the damaged mitochondria releasing reactive oxygen species. Doxycycline was shown to regulate inflammation; however, its effect on NLRP3 in cancer remains largely unknown. Therefore, we sought to determine the effect of doxycycline on NLRP3 regulation in cancer using an in vitro model. NLRP3 was activated in a prostate cancer cell line (PC3) and a lung cancer cell line (A549) before treatment with doxycycline. Inflammasome acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…Therefore, in this study, A549 and PC3 cells were treated with LPS (1 µg/mL; 3 h) to induce NLRP3 and pro-IL-1 β RNA synthesis. Ng (20 µm) was added to initiate inflammasome activation and assembly [ 18 , 19 ]. Antibiotics Az (150 µm) and Cf (100 µg/mL) were added 3 h post LPS treatment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, in this study, A549 and PC3 cells were treated with LPS (1 µg/mL; 3 h) to induce NLRP3 and pro-IL-1 β RNA synthesis. Ng (20 µm) was added to initiate inflammasome activation and assembly [ 18 , 19 ]. Antibiotics Az (150 µm) and Cf (100 µg/mL) were added 3 h post LPS treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous data indicate that some antibiotics, such as nigericin, activate the inflammasome, support inflammation, and have a pro-tumorigenic effect [ 18 ]. In contrast, other antibiotics, such as doxycycline, could oppose inflammasome activation and have an inhibitory effect on cancer cell growth [ 19 ]. Therefore, our data emphasize the importance of testing the effect of antibiotics on inflammasome activation to avoid selection of antimicrobial agent supporting inflammation and tumor progression when used to treat cancer patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Toll-like receptors (TLR) and C-type lectin receptors (CLR) are transmembrane receptors, while retinoic acid-inducible gene (RIG) I-like receptors (RLR) and NOD-like receptors are cytosolic receptors (NLR) ( 14 – 16 ). Currently, the most widely studied inflammasome is the NOD-like receptor protein 3 (NLRP3) inflammasome, which has been shown to mediate the appearance of pyroptosis in a variety of diseases, including dilated cardiomyopathy, ischemic stroke, myocardial ischemia, ICH, inflammation and neoplastic diseases ( 17 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another study found that PD-L1 induced pyroptosis in breast cancer, resulting an immune microenvironment unfavorable for tumor growth ( 20 ). In the last few years, several drugs and compounds and inorganic selenium have been proven to induce pyroptosis in PCa cells and have antitumor potential ( 21 23 ). These findings indicate that pyroptosis may be a potential therapeutic target for PCa patients.…”
Section: Introductionmentioning
confidence: 99%